2023
DOI: 10.1038/s41598-023-31642-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of bone mass in older adults with normal- and overweight derived from the crosstalk with muscle and adipose tissue

Abstract: Lower bone mass in older adults may be mediated by the endocrine crosstalk between muscle, adipose tissue and bone. In 150 community-dwelling adults (59–86 years, BMI 17–37 kg/m2; 58.7% female), skeletal muscle mass index, adipose tissue and fat mass index (FMI) were determined. Levels of myokines, adipokines, osteokines, inflammation markers and insulin were measured as potential determinants of bone mineral content (BMC) and density (BMD). FMI was negatively associated with BMC and BMD after adjustment for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…These differences do not seem to act on insulin resistance ( 25 ), and in fact we detected the irisin relationship with HOMA-2 in both sexes. Unfortunately we did not have a measure to differentiate the lean body weight of the skeletal muscle mass, and we don’t know if serum irisin is more related to any of them, but in previous studies myokines have not shown association with bone parameters ( 27 ). Some studies suggest that sex differences in the adiposity distribution play a role in the different cardiometabolic risk of men and women ( 28 ), but an exact role for irisin in this issue would need future studies.…”
Section: Discussionmentioning
confidence: 97%
“…These differences do not seem to act on insulin resistance ( 25 ), and in fact we detected the irisin relationship with HOMA-2 in both sexes. Unfortunately we did not have a measure to differentiate the lean body weight of the skeletal muscle mass, and we don’t know if serum irisin is more related to any of them, but in previous studies myokines have not shown association with bone parameters ( 27 ). Some studies suggest that sex differences in the adiposity distribution play a role in the different cardiometabolic risk of men and women ( 28 ), but an exact role for irisin in this issue would need future studies.…”
Section: Discussionmentioning
confidence: 97%
“…There are studies suggesting that body fat is the main predictor of BMD at all bone sites [21]. On the other hand, more recent studies suggest a negative relationship between fat mass index and BMD and, at the same time, a positive association between bone and muscle mass [22].…”
Section: Discussionmentioning
confidence: 99%
“…PGC-1α is upregulated in adipose tissue [ 45 , 46 ] following its activation by irisin [ 17 , 39 ]. Irisin-activated adipose, in turn, reciprocally secretes adiponectin, which bolsters muscle and bone development and metabolism [ 47 , 48 , 49 ]. Brown adipose tissue (BAT) releases a distinct combination of adipokines from white adipose tissues, collectively known as batokines, that regulate the development and metabolism of muscle and collateral tissues [ 50 ].…”
Section: Secretome-mediated Muscle–fat Crosstalkmentioning
confidence: 99%